Dieffenbachia toxicity in paediatric oral cavity and its management: A case report - Syahrir, Syakriani; Wijaya, Wiwik E.; Ardiansya, Reza (Hasanuddin University, 2024)
Background: We report a case of intoxication caused by Diefenbachia plant. A 7-year-old boy came to the pediatric dentistry department with complaints of pain in the oral cavity, especially in the tongue and buccal mucosa, tongue swelling, itching, burning, difficulty swallowing, weak condition, vomiting and abdominal pain after it was known that a few hours earlier while playing with his peers he was asked to eat ornamental plants around the house. While in the emergency room, treatment was given with lactated Ringer's infusion, 5 mg dexamethasone injection intra venously, 7 mg diphenhydramine injection intra venously and then decided to be hospitalised. Objective: To report a case of Dieffenbachia toxicity in the oral cavity especially in children. Conclusion: The paediatric patient whose oral cavity was exposed to Diefenbachia recovered with supportive care on day 5. Obtaining history from the patient regarding the plant involved is very important. Paediatric dentists must still be aware of other possibilities that can risk damaging the soft tissues of the oral cavity and can even cause death if not treated properly and quickly even though the patient can recover very well